(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
As widely known plants are divided into many categories, one of them is the herbs; which have been always used as effective remedies to treat many health issues. One of these remedies belongs to our plant under study Pimpinella anisum (anise), which belongs to Umbelliferae family, that has been characterized as an aromatic plant used in traditional medicine as carminative, disinfectant, and galactagogue. Anise dry seeds were collected from Iraqi herbal market to investigate their chemical constituents by using two methods: one of them hydrodistillation method using Clevenger apparatus in which oil sample was collected and then analyzed by GC/MS and revealed the presence of anethol as the major constituent with percentage of 82.91 % of the oil; the second method was alcoholic extraction by Soxhlet apparatus with ethanol till exhaustion then the extract was concentrated by evaporation under vacuum, after that partition with ethyl acetate was done, the ethanol layer was discarded while the ethyl acetate layer was concentrated under vacuum, the collected fraction were analyzed by TLC comparing it with standard Scopoletin .Phytochemical screening proved that the plant contain Scopoletin and was confirmed by comparing Rf value of the sample with the standard in three different solvent systems.